Trilhando pelos solos: um projeto de ensino - Nishizima, Mariana Lopes [UNESP]; Moraes, Ana Paula da Silva [UNESP]; Anjos, Felipe Kenji dos [UNESP]; Nunes, João Osvaldo Rodrigues [UNESP]; Veríssimo, Victor Emmanuel Albertin [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The extension project Treading the soil, has as main proposal disseminate knowledge about the importance of conservation and maintenance of the natural resource soil to society. Soils serve as the basis for human life, since all the food production depends on its use. Thus, it is extremely important see the soils as a tool on the recognition of the importance of this natural source as an environmental formative element. In the last years, a lot of information has been spread about soil, especially about the impacts and its consequence, due the misuse by the society. However, a little is discussed about the preventive measures as well its sustainable use of resources related to teaching soil in shcools. In this way, this is one of the main points of the project Treading the Soil.

O projeto de extensão Trilhando pelos solos, tem como proposta principal, divulgar os conhecimentos sobre a importância da conservação e manutenção do recurso natural solos para a sociedade. Os solos servem de base para a vida humana, já que toda produção alimentar depende de seu uso. Desta forma, é de extrema relevância o ensino de solos como ferramenta na conscientização da importância deste bem natural como elemento formador do ambiente. Nos últimos anos, muito tem se divulgado sobre os solos, principalmente a seu respeito dos impactos e suas consequências, devido ao mau uso pela sociedade. Porém, pouco se discute a respeito das medidas de prevenção e de uso sustentável dos recursos relacionados ao ensino de solos nas escolas. Desta forma, este é um dos pontos fundamentais do Projeto Trilhando Pelos Solos.
Keywords: Soils; Education; Environment; Solos; Ensino; Meio ambiente